The Political Economy of Fiscal Reform in Latin America: The Case of Argentina - Alejandro Bonvecchi (Inter-American Development Bank (IDB), 2010)
This paper investigates the political economy of fiscal reform activism in Argentina since the late 1980s. Between 1988 and 2008, tax legislation was changed 83 times, fiscal federal rules 14 times, and budgetary institutions sixteen times. Tax and budgetary reforms moved from centralizing revenue sources and spending authority in the federal government to mild decentralization lately. Fiscal federal rules combined centralization of revenues and management in the federal government with short-term compensations for the provinces. This paper contends that reform activism can be explained by the recurrence of economic and policy shocks while reform patterns may be accounted for as consequences of the decreasing political integration of national parties in a polity whose decisionmaking rules encourage the formation of oversized coalitions. The decrease in political integration weakened the national party leaderships ability to coordinate intergovernmental bargaining, and strengthened the local bosses and factions needed to form oversized coalitions.
Keywords: H77; H61; H20; 330; Public finance; Budget; Taxes; Federalism; Intergovernmental relations